Leverage, Tata Kelola Perusahaan, dan Manajemen Laba Riil - Ananto Prabowo; Indah Sari Pangestu (Universitas Winaya Mukti, 2021)
Earnings management is conducted by key internal personels within a firm through the utility of accounting policy judgements which then mislead financial reports. The level of leverage and corporate governance have the ability to influence the degree of earnings management implementation. This research has an objective to examine the leverage and corporate governance mechanisms influence on real earnings management. This research population is included in 50 companies with the best corporate governance implementation in Indonesia for the period of 2012-2018. By using the purposive sampling method, 126 observations fit the sample criteria. This research uses a quantitative approach and secondary data with a random effects’ regression model. This research shows leverage and corporate governance mechanisms, when combined, affect real earnings management. This research's supplementary results show that leverage cannot limit real earnings management practice and consecutively on corporate governance mechanism. Independent board of commissioner negatively and significantly exert influence on real earnings management, followed by the audit committee, reducing real earnings management practice. Meanwhile, institutional and managerial ownership do not present a significant merit on real earnings management. This research implicates the policy maker in justifying good corporate governance and practioners to look upon the possibility of real activities manipulation.